Fast and sensitive determination of sulfur dioxide in herbal medicines by microchip-based field asymmetric-wave ion mobility spectrometry. Issue 3 (16th December 2014) - Wang, Xiaozhi; Zhao, Weijun; Li, Lingfeng; Wang, Xiangyang; Li, Peng; Wang, Yu; Luo, Jikui
Abstract : This paper reports a new method for the direct determination of SO2 in HMs using fast field asymmetric-wave ion mobility spectrometry (FAIMS) coupled with a headspace air bubbling method. Abstract : Sulfites (sulfur dioxide) and inorganic sulfites are types of food additives and preservatives, widely used in the production of food and herbal medicines (HMs). However, the overingestion of sulfites and its associates are harmful to human health and may cause medical complications. Various methods and instruments have been developed for measuring sulfites in foods and HMs, but they typically suffer from many issues, such as high detection limitation, inaccurate and non-reliable results, time and labor-intensive sample preparation, and high cost. Herein, we present a fast, sensitive, and quantitative method to determine sulfites in HMs using field asymmetric-wave ion mobility spectrometry (FAIMS) coupled with a headspace bubbling method. The headspace air bubbling method is effective and efficient at generating stable sulfur dioxide (SO2 ) in the gas phase for FAIMS analysis. It allows sulfites with a concentration down to 1 mg kg −1 to be easily detected by this new method in 20 min, much shorter than with current technologies. The limits of detection (LOD) and limits of quantification (LOQ) are 1 mg kg −1 and 3 mg kg −1 in HMs, respectively. The new method is of great significance to ensure medical safety and for HM production quality control.